Investigating dyeing properties of regenerated bamboo material dyed with reactive and direct dyes - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2011)
Investigating dyeing properties of regenerated bamboo materials dyed with reactive and direct dyes Because of its inherent antibacterial property, soft handle, easy dyeability and many other better properties over the other regenerated cellulosic fibers, the use of regenerated bamboo fiber is increasing in the textile industry. In this research, 100% regenerated bamboo fabric samples were used throughout. The fabrics were enzymatically pretreated, bleached and dyed with reactive dyes (C.I. Reactive Blue 19, C.I. Reactive Red 239 and C.I. Reactive Yellow 186) to investigate the effect of the pretreatment on the physical and dyeing properties of the materials. In another part of this research, the dye uptake properties of reactive and direct dyes (C.I. Direct Blue 90, Cl. Direct Red 83:1 and C.I. Direct Yellow 98) were studied under atmospheric conditions. In addition, the microwave heat dyeings were carried out with the reactive dyes, and the properties of the dyed materials were compared with those of the conventionally dyed materials.
Keywords: bamboo fabric; exhaust dyeing; reactive dyes; direct dyes; SEM image; color fastness; microwave heat dyeing